Autumn diet of harbour seals ( Phoca vitulina) at Prins Karls Forland, Svalbard, assessed via scat and fatty-acid analyses - Andersen, Signe M; Lydersen, Christian; Grahl-Nielsen, Otto; Kovacs, Kit M (Canadian Journal of Zoology, 2004)
This study used hard-part analyses from scats (n = 117) and stomachs (n = 3) to investigate the diet of high Arctic harbour seals (Phoca vitulina L., 1758) living on Prins Karls Forland, Svalbard, in early autumn. Additionally, it compared the results of fatty-acid analyses of the seals' blubber versus that of potential prey with the findings of the more traditional diet assessment method. Svalbard harbour seals appear to be opportunistic, polyphagous feeders similar to the situation in other parts of their range. Members of the cod-family, and secondarily the sculpin-family, dominated the diet of harbour seals on Svalbard. Small fish comprised most of the diet of the harbour seals; invertebrates appeared to be insignificant. Atlantic cod (Gadus morhua L., 1758) was the most important species in the diet in terms of biomass, whereas polar cod (Boreogadus saida (Lepechin, 1774)) was the most frequently consumed prey. Our comparison between hard-part diet analyses and fatty acids is far from definitive, but it indicates a general influence of the diet on the fatty-acid composition of the inner blubber layer. However, it also suggests systematic selective processes in the incorporation of fatty acids into the blubber. Observed differences between the fatty-acid composition of the different blubber layers and possible differences between sex and age classes warrant further investigation.